Polymorphism of the Two Genes Encoding Catecholamine Degradation Enzymes (COMT and MAOA) in the Hadza and Datoga African Ethnic Populations - Fekhretdinova, D. I.; Sukhodolskaya, E. M.; Shibalev, D. V.; Lazebnyy, O. E.; Butovskaya, M. L.; Ryskov, A. P.; Vasil’yev, V. A. (Molecular genetics, microbiology and virology, 2018)
This paper reports a molecular genetics analysis of the loci of two genes in the catecholamine degradation system (COMT rs4680 and MAOA-uVNTR) in samples from the Hadza ( n = 353) and Datoga ( n = 465) African ethnic populations. The results of pairwise comparisons of the COMT rs4680 locus allele and genotype frequency distribution revealed a statistically significant difference between men from the Hadza and Datoga populations ( p < 0.001), while the differences observed between women from these two tribes remained below the significance threshold ( p = 0.064; p = 0.076). In the Hadza population, we have also observed a statistically significant increase in the portion of G/A heterozygotes and a decrease in the portion of A/A homozygotes among women (0.576 and 0.127, respectively) compared with men (0.482 and 0.231, respectively). In the case of the MAOA-uVNTR locus, no statistical differences in the allele frequency distribution were found between the men from the two populations ( p = 0.993). Women also showed no statistical differences in either allele ( p = 0.229) or genotype ( p = 0.057) frequencies. Moreover, in each tribe, we observed no differences in allele frequencies in the MAOA-uVNTR locus between the men and women of the same tribe. The obtained data may be further used to detect connections between gene variants and different forms of aggressive behavior in human beings.